Lifelong behavioral and neuropathological consequences of repetitive mild traumatic brain injury. Issue 1 (14th December 2017) - Mouzon, Benoit C.; Bachmeier, Corbin; Ojo, Joseph O.; Acker, Christopher M.; Ferguson, Scott; Paris, Daniel; Ait‐Ghezala, Ghania; Crynen, Gogce; Davies, Peter; Mullan, Michael; Stewart, William; Crawford, Fiona
Abstract: Objective: Exposure to repetitive concussion, or mild traumatic brain injury (mTBI), has been linked with increased risk of long‐term neurodegenerative changes, specifically chronic traumatic encephalopathy (CTE). To date, preclinical studies largely have focused on the immediate aftermath of mTBI, with no literature on the lifelong consequences of mTBI in these models. This study provides the first account of lifelong neurobehavioral and histological consequences of repetitive mTBI providing unique insight into the constellation of evolving and ongoing pathologies with late survival. Methods: Male C57BL/6J mice (aged 2–3 months) were exposed to either single or repetitive mild TBI or sham procedure. Thereafter, animals were monitored and assessed at 24 months post last injury for measures of motor coordination, learning deficits, cognitive function, and anxiety‐like behavior prior to euthanasia and preparation of the brains for detailed neuropathological and protein biochemical studies. Results: At 24 months survival animals exposed to r‐mTBI showed clear evidence of learning and working memory impairment with a lack of spatial memory and vestibule‐motor vestibulomotor deficits compared to sham animals. Associated with these late behavioral deficits there was evidence of ongoing axonal degeneration and neuroinflammation in subcortical white matter tracts. Notably, these changes were also observed after a single mTBI, albeit to a lesser degree than repetitive mTBI. Interpretation: In this context, our current data demonstrate, for the first time, that rather than an acute, time limited event, mild TBI can precipitate a lifelong degenerative process. These data therefore suggest that successful treatment strategies should consider both the acute and chronic nature of mTBI.